2020
DOI: 10.3390/jcm9020581
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low-Dose Radioiodine Ablation in Low- and Intermediate-Risk Differentiated Thyroid Cancer: A Retrospective Comparative Analysis

Abstract: (1) Background—low-dose radioiodine ablation is an accepted strategy for the treatment of low- and intermediate-risk thyroid carcinomas, although there is no international consensus. The aim of this study is to describe the clinical experience with low-dose radioiodine ablation in patients with low- and intermediate-risk thyroid cancer compared to high-dose ablation. (2) Methods—174 patients with low- and intermediate-risk thyroid cancer, 90 treated with low-dose ablation and 84 treated with high-dose ablation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The authors found the same results even in younger patients (HR = 0.64; CI 95%:0.45–0.92, p = 0.016) [ 63 ]. Considering RAI activity, lower iodine protocols have been proposed for intermediate-risk patients with mainly lower risk features, but controversial results are available [ 53 , 64 , 65 , 66 , 67 ] ( Table 2 ) and different practices can be observed according to each centers’ experience.…”
Section: Radioiodine Treatment Goalsmentioning
confidence: 99%
“…The authors found the same results even in younger patients (HR = 0.64; CI 95%:0.45–0.92, p = 0.016) [ 63 ]. Considering RAI activity, lower iodine protocols have been proposed for intermediate-risk patients with mainly lower risk features, but controversial results are available [ 53 , 64 , 65 , 66 , 67 ] ( Table 2 ) and different practices can be observed according to each centers’ experience.…”
Section: Radioiodine Treatment Goalsmentioning
confidence: 99%
“…More recently, other researchers reported that high dose of 131 I resulted in a successful ablation more often than low dose (3,7,8), especially in those patients with positive anti thyroglobulin antibodies or higher stimulated thyroglobulin levels at the moment of radioiodine ablation (8).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of randomized and observational studies published in 2007 was inconclusive as to whether low-dose 131 I (1.1GBq [30 mCi]) was associated with rates of ablation success similar to -or lower than -rates obtained with high-dose radioiodine (3.7 GBq [100 mCi]) [6]. More recently, other researchers reported that high dose of 131 I resulted in a successful ablation more often than low dose [3,7,8], especially in those patients with positive anti thyroglobulin antibodies or higher stimulated thyroglobulin levels at the moment of radioiodine ablation [8].…”
Section: Discussionmentioning
confidence: 99%